INTERNATIONAL BUSINESS ENVIRONMENT: ANTECEDENT AND PROSPECTS - Maxwell Nwinye (Scholars Digest Publishing, 2025)
International business environment appears to be more multifaceted, risky, and dynamic because of numerous factors affecting the business operations. Managements have to streamline their strategies and leadership styles in accordance to the laws of host counties and regions of the world. Business environment risk has increased responsibilities of managements to improve their ability on production, skills acquisition, and marketing of global products. The typical challenges affecting foreign firms or multinational companies are the external uncontrollable factors such as economic, technological, political, sociocultural, and legal factors that hinder company’s operations across the national frontiers. International business environment is also associated with relative high risks and the projected return on investments in the global market. Organizations should train employees to have knowledge on how to manage dynamic environment necessary in maintaining competitive advantage. This paper explores prospects and nature of international business environment, highlighting how environmental factors could affect the operations of companies abroad.
Keywords: Economic, political, legal, technological, sociocultural factors.